Adaptasi Waria: Studi Kasus Komunitas Waria di Kabupaten Pangkep - Tanjung, Faisal (PREDESTINASI, 2020)
This study aims to see (1) Know how to read waria in the community (2) To see how public acceptance of waria is. The type of research used is descriptive qualitative which describes the adaptation of the transgender community by taking the location in Pa'doang-doangan Village, Pangkajene District, Pangkep Regency. Information retrieval was carried out by purposive sampling, and obtained 14 people. The data techniques used were observation, interview and documentation. The results showed that 1) The adaptation process carried out by the transgender community in Pa`doang-doangan Village is by associating and always interacting with the community and how they uphold the values of mutual respect for each individual both in a young or adult environment and the most important thing is to keep them ethical. In addition, they provide the best service to each of their customers and are active in community social activities so as to create a high emotional sense with community members. 2) The existence of transgender women in society at first received social pressures but slowly they were able to accept it well in society. The manifestation of the acceptance of the existence of the waria community in Pa`doang-doangan Village is that they are not only accepted in their social environment, but they get legitimacy from the local government. Now they have the same social role in their social environment.